The Relationship Between Organizational Learning and Innovation: A Case Study of Learning Organizations - Agarwal, Nidhi; Kumar, Puneet (Journal of Knowledge Management Practice, 2024)
This article examines how organisational learning and innovation interact. Innovation, which boosts productivity and competitiveness, requires workplace learning. This study examines the interactions of these two main variables holistically. 300 employees from 100 enterprises and 100 stakeholders with close relationships to these organisations are polled, interviewed, and their corporate records evaluated in a mixed-methods study. We assess how well these companies’ organisational learning practices foster innovation. This study’s findings on organisational learning and creativity illuminate various aspects, including knowledge generation, sharing, application, and reflection. The study also examines organisational barriers to innovation and learning. This study analyses employee and stakeholder perspectives to better understand organisational learning and innovation. These findings affect the development of learning, innovation, and corporate performance approaches. This study helps companies capitalise on the synergy between organisational learning and innovation to grow and compete.